PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOTOR YAMAHA TYPE NMAX DI BANJARMASIN - Rika Sylvia; - Mailiana (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, The purpose of this study was to determine whether product quality and price have a simultaneous and partial effect, as well as to determine which of the variables of product quality and price have the most dominant influence on purchasing decisions for a Yamaha motorbike type NMax. The population of this research is consumers who buy a Yamaha motorbike type NMax. While the sample of consumers taken was 100 people. Types and sources of data in the form of primary data obtained by using a questionnaire distributed to consumers as respondents, complemented by secondary data obtained from various references. Multiple Linear Regression Method is used to test the proposed hypothesis. The results of the research on product quality and price have a significant effect on purchasing decisions, both simultaneously and partially with statistical results using SPSS version 22.0 as follows Y = - 0.734 + 0.441 X1 + 0.727 X2 + e, meaning that the test results for each variable consist of Product quality (X1) with a coefficient of 0.441 and price (X2) with a coefficient of 0.727 have a positive effect both partially and simultaneously on purchasing decisions (Y). Meanwhile, the value of R Square is 0.765, which means that the variable contribution of product quality and price is 76.5% affecting consumer purchasing decisions in choosing a Yamaha NMax type motorcycle, while the remaining 23.5% is influenced by other variables.